Effects of charcoal stripped fetal bovine serum and titanium surface microtopography on growth and osteogenic differentiation of human bone marrow stromal cells - Chonticha Chookiartsiri (Prince of Songkla University, 2015)
Thesis (M.Sc., Oral and Maxilofacial Surgery)--Prince of Songkla University, 2014